2018
DOI: 10.1111/eje.12351
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Dental Scrubs Ceremony to define professional identity and teach professionalism to dental undergraduates; lessons learned

Abstract: Introduction The UK General Dental Council stipulates that professionalism is a key aspect of the teaching and training of dental students. However, dental educators highlight that teaching dental student's professionalism can be challenging and students often rate this teaching activity negatively. This article documents a teaching initiative at one UK Dental School that aimed to strengthen the professionalism curriculum by introducing a Dental Scrubs Ceremony for second‐year students. Materials and method Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…A large proportion of respondents saw the ceremony as a way of welcoming new students to the profession. Recently the Bristol Dental School reported similar results with the introduction of a Dental Scrubs Ceremony, inspired by the WCC in the US. That study revealed that the dental students appreciated the inherent symbolism in the ceremony and found it to be worthwhile .…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…A large proportion of respondents saw the ceremony as a way of welcoming new students to the profession. Recently the Bristol Dental School reported similar results with the introduction of a Dental Scrubs Ceremony, inspired by the WCC in the US. That study revealed that the dental students appreciated the inherent symbolism in the ceremony and found it to be worthwhile .…”
Section: Discussionmentioning
confidence: 71%
“…Recently the Bristol Dental School reported similar results with the introduction of a Dental Scrubs Ceremony, inspired by the WCC in the US. That study revealed that the dental students appreciated the inherent symbolism in the ceremony and found it to be worthwhile . In a study of medical students, Brown et al .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…An emphasis on quota requirements that rely on the completion of a specific number of dental procedures to demonstrate competence detracts from the qualitative development of professionalism 19 . The traditional white coat ceremonies, which facilitate the induction of the professional values and virtues, 20 and experiences like the donor letter program, which share letters from the families of the deceased with the dental students, help to instill empathy in future dental professionals 21 . However, both methods focus on a cognitive and top‐down approach that is disconnected with behaviors or a bottom‐up approach.…”
Section: Discussionmentioning
confidence: 99%